1998
DOI: 10.1590/s0100-879x1998000100024
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines as determinants of resistance and pathology in human Schistosoma mansoni infection

Abstract: The role of different cytokines in the peripheral blood mononuclear cell (PBMC) proliferative response and in in vitro granuloma formation was evaluated in a cross-sectional study with patients with the different clinical forms and phases of Schistosoma mansoni infection, as well as a group of individuals naturally resistant to infection named normal endemic (NE). The blockage of IL-4 and IL-5 using anti-IL-4 and anti-IL-5 antibodies significantly reduced the PBMC proliferative response to soluble egg (SEA) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
60
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 23 publications
5
60
0
1
Order By: Relevance
“…Therefore, PGE 2 -driven IL-10 production in the skin following infection may play a significant role in the immunomodulation of inflammatory responses in the skin of infected animals. These findings are similar to those reported by Hoffmann et al (32), who state that a major consequence of schistosome-induced IL-10 production is to 3,125.50 Ϯ 213.5 * Con A ϩ keratinocyte supernatant (50 g/ml) 2,214.10 Ϯ 102.4 * Con A ϩ 14 g/ml fraction IV ϩ 10 g/ml anti-IL- 10 10,987.78 Ϯ 321.8 Con A ϩ 50 g/ml keratinocyte sup ϩ 10 g/ml anti-IL- 10 12,596.14 Ϯ 457.0 down-regulate the immune responses of the host against the parasite. However, this subdued inflammation is seen only so long as live parasites are present in the skin (3), suggesting that the PGE 2 / IL-10-inducing activity is present only in the secretions of the tissue-migrating parasites.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, PGE 2 -driven IL-10 production in the skin following infection may play a significant role in the immunomodulation of inflammatory responses in the skin of infected animals. These findings are similar to those reported by Hoffmann et al (32), who state that a major consequence of schistosome-induced IL-10 production is to 3,125.50 Ϯ 213.5 * Con A ϩ keratinocyte supernatant (50 g/ml) 2,214.10 Ϯ 102.4 * Con A ϩ 14 g/ml fraction IV ϩ 10 g/ml anti-IL- 10 10,987.78 Ϯ 321.8 Con A ϩ 50 g/ml keratinocyte sup ϩ 10 g/ml anti-IL- 10 12,596.14 Ϯ 457.0 down-regulate the immune responses of the host against the parasite. However, this subdued inflammation is seen only so long as live parasites are present in the skin (3), suggesting that the PGE 2 / IL-10-inducing activity is present only in the secretions of the tissue-migrating parasites.…”
Section: Discussionsupporting
confidence: 90%
“…It is baffling, especially in immunized animals, how the skin-stage schistosomula are able to induce an overbearing IL-10 response in a milieu predominated by IFN-␥-producing cells (4 -7). IL-10 has been implicated in the down-regulation of various immune responses against S. mansoni in both mice (8,9) and humans (10,11). Therefore, it is possible that this early IL-10 response in the skin and draining lymph nodes may play a pivotal role in parasite establishment by modulating the Th1-type responses (11,12).…”
mentioning
confidence: 99%
“…The selected group lives in the endemic area of Virgem das Graças, state of Minas Gerais (MG), Brazil. After several stool examinations by the Kato-Katz method and negative findings over years of studies, these patients had been referred to as "normal endemic" (Corrêa-Oliveira et al 1998, Gazzinelli et al 2006. The saline gradient method identified a positive infection rate for S. mansoni of 25% based on analysis of two faecal samples of 500 mg. On the other hand, two sets of 12 Kato-Katz slides per each individual revealed a prevalence of 20% of infection.…”
Section: Discussionmentioning
confidence: 99%
“…This assay showed that Para (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29), Para (210-226) and Para (355-371) were able to bind to 100% (8/8) of the HLA-DR molecules used in this assay,…”
Section: Paramyosin Peptide Binding To Mhc Class II Moleculesmentioning
confidence: 90%
“…A recent study performed with mice infected with S. mansoni has shown that chronic infection is related to IL-10 production, which can be responsible for the Th2 type of immune response observed after egg deposition [25]. IL-10 mediates IFN-γ suppression in human schistosomiasis, and therefore T cell proliferative responses to S. mansoni antigens in infected individuals are reduced [26]. However, we believe that preferential recognition of Para (210-226) by the RR group compared to the SR group cannot be attributed to immunomodulation mediated by IL-10 produced by the SR group, as no statistically significant difference was observed between both groups regarding proliferative responses to PHA.…”
mentioning
confidence: 99%